2013
DOI: 10.1007/s11552-013-9509-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Palmaris Longus Muscle and its Relationship with Grip and Pinch Strength: A Study in a Turkish Pediatric Population

Abstract: Clinical studies generally reveal a trend of variation in the reported prevalence of the palmaris longus (PL) muscle absence. The aim of this study was to find an answer to the question of whether the congenital absence of tendon would affect hand functions or not. A total of 585 subjects, comprised of 305 males and 280 females, were included in our study. Mean age was 8.9±1.4 standard deviation within a range of 6-11. For both sexes, the groups were divided further into three subgroups including 6-7, 8-9, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 12 publications
2
27
0
2
Order By: Relevance
“…These authors concluded that there was no significant difference in hand strength between the two groups. This was also determined in a pediatric population by Cetin et al [13]. As for grip strength, they found that the presence of the PLM did not create a difference in general.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…These authors concluded that there was no significant difference in hand strength between the two groups. This was also determined in a pediatric population by Cetin et al [13]. As for grip strength, they found that the presence of the PLM did not create a difference in general.…”
Section: Introductionmentioning
confidence: 58%
“…Some authors have found that absence of the PLM was not significantly correlated with decreased grip or pinch strength measurements [12,13]. Cetin et al [13] on the other hand, reported that having a PLM increased the pinch strength in the fourth and fifth finger of the hand, especially in the right hand.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…10 In such individuals, use of the FCR motor branch as a donor for nerve transfer is contraindicated, because this will prevent any FCU tendon transfer to the EDC if nerve repair fails.…”
Section: And Fdsmentioning
confidence: 99%